2018
DOI: 10.1042/bsr20180749
|View full text |Cite
|
Sign up to set email alerts
|

The association between the miR-146a rs2910164 C>G polymorphism and Kawasaki disease in a southern Chinese population

Abstract: miR-146a plays a critical role in innate immune and inflammatory responses. Kawasaki disease involves immune-mediated inflammatory responses, which leads to vascular endothelial injury. However, there has been no study on the association between the miR-146a rs2910164 C>G polymorphism and Kawasaki disease risk. We enrolled 532 Kawasaki disease patients and 623 healthy controls from southern Chinese population, and the miR-146a rs2910164 C>G polymorphism was genotyped by the TaqMan method. There was no evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The statistical analysis procedures have been described previously. 29 3 | RESULTS Table 1 shows the demographic characteristics of KD cases and controls. Mean ± SD age was 29.12 ± 24.68 months (range 1-166 months) for KD patients and 23.14 ± 21.72 months (range 1-166 months) for controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis procedures have been described previously. 29 3 | RESULTS Table 1 shows the demographic characteristics of KD cases and controls. Mean ± SD age was 29.12 ± 24.68 months (range 1-166 months) for KD patients and 23.14 ± 21.72 months (range 1-166 months) for controls.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between the P2RY12 polymorphisms and KD were assessed with stratification by age, sex, CAA and GCAA presence. The statistical analysis procedures have been described previously …”
Section: Methodsmentioning
confidence: 99%
“…Our previous study reported that miRNA-146a rs2910164 C>G may not be associated with Kawasaki disease susceptibility in children from South China. 18 We found that miRNA-137 rs1625579 T>G is associated with the onset of Kawasaki disease in the same population in children younger than 1 year old. 16 To our knowledge, this report is the first on the association of miRNA-196a2 rs11614913 T>C with Kawasaki disease susceptibility among children in South China.…”
Section: Discussionsmentioning
confidence: 67%
“…The control group was composed of 623 healthy Chinese children who went to the hospital for physical examination in the same period. [16][17][18] Peripheral venous blood was taken from each child to extract DNA.…”
Section: Study Subjectsmentioning
confidence: 99%
“…All participants recruited were unrelated Chinese Han individuals from southern China. A total of 623 healthy controls and 532 patients diagnosed with KD were recruited from January 2012 to January 2017 as we described previously . Two milliliters of fresh blood was collected from each participant, and 200 µL of each blood sample was employed to extract DNA.…”
Section: Methodsmentioning
confidence: 99%